E-246 Multicenter US clinical experience with the scepter mini balloon catheter. (23rd July 2022) - Salem, M; Ostmeier, S; Hoang, A; Cortez, G; Naamani, K; Abbas, R; Gooch, M; Jabbour, P; Kan, P; Hanel, R; Tanweer, O; Jankowitz, B; et al.
Abstract : Introduction: Distal catheter navigability and imprecise delivery of embolic agents remain the two most important limitations encountered during endovascular liquid embolization of cerebrospinal vascular malformations. The new dual lumen Scepter-Mini Balloon (SMB) microcatheter was introduced with the aim of overcoming these limitations encountered with conventional microcatheters with few small single-center reports suggesting favorable results; however, multicenter data remain lacking. Methods: Series of consecutive patients undergoing endovascular embolization utilizing SMB were extracted from prospectively maintained registries in 7 North American cerebrovascular centers (November 2019- December 2021). Results: 42 patients undergoing embolization utilizing the SMB were included (median age 58.5; 55.9% females). Cranial dural arteriovenous fistula (dAVF) embolization was the most common indication (55.8%) followed by cranial arteriovenous malformation (AVM) embolization (20.6%). Staged/pre-operative embolization was done in 23.5% of the cases, with 94.1% of procedures utilizing Onyx-18 as the embolic agent. The majority of procedures utilized the transarterial approach (88.3%), while arterial flow arrest utilizing Scepter-Mini concurrently with transvenous embolization was utilized in 4.7% of procedures. Femoral access and triaxial setups were utilized in most procedures (85.2% and 59%, respectively). The median vessel diameter where balloon was inflated of 1.7mm, with median 1.5cc of injected embolic material per procedure. Technical failures were encountered in 9.5% of procedures requiring replacement with other microcatheters without clinical sequalae in any of the patients, with SMB-related procedural complications of 2.4%. Complete occlusion (100%) or >50% occlusion on last follow-up were documented in 78.3% of the cases, with unplanned retreatments needed in 2.4% of the cases, over a median of 3.4 months of follow-up. Conclusion: The Scepter-Mini Balloon microcatheter is a useful new adjunctive device for balloon-assisted embolization of cerebrospinal vascular malformations requiring distal access with a high technical success rate, favorable outcomes, and reasonable safety profile. Disclosures: M. Salem: None. S. Ostmeier: None. A. Hoang: None. G. Cortez: None. K. Naamani: None. R. Abbas: None. M. Gooch: None. P. Jabbour: None. P. Kan: None. R. Hanel: None. O. Tanweer: None. B. Jankowitz: None. J. Heit: None. J. Burkhardt: None.